ANTIMICROBIAL POTENTIAL OF TEA TREE, CLOVE, BASIL AND THYME ESSENTIAL OILS AGAINST BACTERIAL ISOLATES OF BOVINE WOUNDS - F. Leghari; A. A. Kamboh1; R. A. Leghari; N. A. Korejo; K. K. Malhi (Journal of Animal and Plant Sciences, 2021)
The present research aimed to investigate the individual and combined antimicrobial potential of plant essential oils (EOs) viz., tea tree (Melaleuca alternifolia), clove (Syzygium aromaticum), basil (Ocimum basilicum), and thyme (Thymus vulgaris) against bovine wound isolates. Staphylococcus aureus, Streptococcus pneumoniae, Streptococcus pyogenes, Escherichia coli and Klebsiella spp. were isolated from bovine wound samples. Inhibition of microbial growth via disk diffusion method and minimum inhibitory concentration (MIC) was analyzed for EOs and standard antibiotics both individually and in combination. Tea tree and clove produced significantly higher (p≤0.05) inhibitory effects against all the bacteria compared to one or other EOs and standard antibiotics. Basil+ neomycin, thyme+ ampicillin and tea tree+ ampicillin exhibited synergisms against all the wound isolates except Klebsiella spp. The MIC result indicated that clove followed by basil and tea tree exhibited significantly lower (p≤0.05) MIC values against tested isolates compared to one or other EOs and antibiotics. The combination of thyme neomycin and clove norfloxacin exhibited a significantly lower (p≤0.05) MIC against S.pyogenes and E.coli  compared to other combination of EOs and antibiotics. Likewise, the combination of basil oxytetracycline and clove norfloxacin exhibited a significantly lower (p≤0.05) MIC against S.pneumoniae compared to one or other combinations of EOs and antibiotics. These results demonstrated the significant antimicrobial potential of EOs against wound isolates; individually tea tree and clove showed superior effects, whereas combinations of basil+ neomycin, thyme+ ampicillin and tea tree+ ampicillin showed synergisms compared to one or other EOs and antibiotics.
Keywords: antibacterial; bovine wound; plant essential oil; synergistic effect